Study of the kanban control system - Lee, Han Siang. (2011)
Over the years, much attention has been given to the study of the pull system to reduce in-process inventory and improve work efficiency. Kanban Control Systems are widely used to control the release of parts in multi-stage manufacturing systems operating under a pull mechanism. Considerable research has since been on study of the individual manufacturing systems for multi stage and single product. However, not much research has been done for comparison work.